2017
DOI: 10.3802/jgo.2017.28.e36
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma fibrinogen levels and prognosis of epithelial ovarian cancer: a cohort study and meta-analysis

Abstract: ObjectiveTo evaluate the effect of elevated plasma fibrinogen levels on the prognosis of epithelial ovarian cancer (EOC).MethodsWe reviewed the data of 217 patients with advanced-stage EOC between 2000 and 2012, and investigated the prognostic role of elevated plasma fibrinogen levels compared with serum CA-125 levels, neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR). For further evaluation, we performed a meta-analysis using 5 cohort studies published to July 2015, including our coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…A recent meta-analysis of data from 13 studies (n ¼ 3,467) showed that both high neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio are associated with unfavorable prognosis of patients with EOC (25). In addition, elevated levels of pretreatment plasma D-dimer, Fbg, and PLT were found useful in predicting disease progression and survival outcomes of patients with EOC (26)(27)(28). These reports support our findings; indeed, additional studies using independent datasets are required to investigate how we can utilize this preoperative blood signature for accurate prognostic assessment of patients with EOC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of data from 13 studies (n ¼ 3,467) showed that both high neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio are associated with unfavorable prognosis of patients with EOC (25). In addition, elevated levels of pretreatment plasma D-dimer, Fbg, and PLT were found useful in predicting disease progression and survival outcomes of patients with EOC (26)(27)(28). These reports support our findings; indeed, additional studies using independent datasets are required to investigate how we can utilize this preoperative blood signature for accurate prognostic assessment of patients with EOC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, much attention has been paid to the association between hypercoagulation and malignancy progression in recent years 29,30. Accumulating evidence indicates that the activation of the coagulation cascade plays a key pathophysiological role during tumor progression 31.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fibrinogen (Fib), a major protein in the blood clotting process, is associated with cancer 6 . Although recent studies have reported that plasma Fib was related to cancer progression and prognosis in various cancers [7][8][9] , the role of plasma Fib in EC remains controversial [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%